Dynamics of rotating non-linear thin-walled composite beams: analysis of modeling uncertainties - Piovan, Marcelo Tulio (2012)
In this article a non-linear model for dynamic analysis of rotating thin-walled composite beams is introduced. The theory is deduced in the context of classic variational principles and the ﬁnite element method is employed to discretize and furnish a numerical approximation to the motion equations. The model considers shear ﬂexibility as well as non-linear inertial terms, Coriolis? effects, among others. The clamping stiffness of the beam to the rotating hub is modeled through a set of spring factors. The model serves as a mean deterministic basis to the studies of stochastic dynamics, which are the objective of the present article. Uncertainties should be considered in order to improve the predictability of a given modeling scheme. In a rotating structural system, uncertainties are present due to a number of facts, namely, loads, material properties, etc. In this study the uncertainties are incorporated in the beam-to-hub connection (i.e. the connection angle and the springs) and the rotating velocity. The probability density functions of the uncertain parameters are derived employing the Maximum Entropy Principle. Different numerical studies are conducted to show the main characteristics of the uncertainty propagation in the dynamics of rotating composite beams.